META-ANALYSIS: SQUAMOUS CELL CARCINOMA CASES ARISING FROM MORBUS HANSEN IN DR. SITANALA CENTRAL HOSPITAL (2011-2021) - Victoria, Francisca; Pribadi, Sweety (Universitas Airlangga, 2023)
Highlights: The majority of SCC cases were observed in males (86%), emphasizing a higher susceptibility of males to this form of cancer compared to females (14%). The study identified an increased risk of SCC particularly among individuals in the 46-55 and 56-65 age groups. The study revealed that a significant proportion of Morbus Hansen patients with SCC had a normal weight, while the occurrence of overweight and obesity was relatively low. Maintaining a healthy body weight may play a role in reducing the risk of SCC in this patient population. Abstract: Introduction: Leprosy, a chronic systemic infection caused by Mycobacterium Leprae, has been associated with the development of cutaneous neoplasms, such as squamous cell carcinoma. The aim of this study was to examine the characteristics of patients diagnosed with squamous cell carcinoma arising from Morbus Hansen (leprosy). Methods: A retrospective analysis of medical records from Dr. Sitanala Central Hospital was conducted, focusing on patients diagnosed with squamous cell carcinoma arising from Morbus Hansen over a 10-year period from 2011 to 2021. Descriptive analysis was performed on the collected data. Result: In this study, out of the twenty-one patients, the majority were male (86%), and the most common age group affected was between 46 and 55 years, accounting for 43% of the cases. Most patients had Morbus Hansen type BL (borderline lepromatous) and had been living with the condition for an average of 23 years. Additionally, a significant number of patients had a normal body mass index (52%) within the range of 20-24.9. Anemia was the main comorbidity observed, affecting 46% of the patients. Conclusion: Examining the clinical profile of these patients helps healthcare providers identify specific characteristics associated with this condition, further research with more comprehensive data is necessary to ensure accuracy. Future studies could also explore potential connections between hypertension, anemia, and squamous cell carcinoma arising from Morbus Hansen.